Bilateral Traumatic Thalamic Hemorrhage: A Rare Clinical Presentation - Mandour, Cherkaoui; Gazzaz, Miloudi; Mostarchid, Brahim EI (Indian Journal of Neurotrauma, 2017)
Bilateral traumatic thalamic hemorrhage is a very rare occurrence, especially after head trauma, and is limited to case reports. The authors present a 27-year-old man, admitted for head trauma causing bilateral thalamic bleeding. Posttraumatic intracerebral bleeding is caused by focal or diffuse axonal injury. Bilateral traumatic thalamic hemorrhage is a rare clinical and radiologic presentation.
Keywords: thalamic; hemorrhage; bilateral; head trauma